A Clinical Approach to Multimodality Imaging in Pulmonary Hypertension - Farrell, Christine; Balasubramanian, Aparna; Hays, Allison G.; Hsu, Steven; Rowe, Steven; Zimmerman, Stefan L.; Hassoun, Paul M.; Mathai, Stephen C.; Mukherjee, Monica (Frontiers in Cardiovascular Medicine, 2022)
Pulmonary hypertension (PH) is a clinical condition characterized by progressive elevations in mean pulmonary artery pressures and right ventricular dysfunction, associated with significant morbidity and mortality. For resting PH to develop, approximately 50-70% of the pulmonary vasculature must be affected, suggesting that even mild hemodynamic abnormalities are representative of advanced pulmonary vascular disease. The definitive diagnosis of PH is based upon hemodynamics measured by right heart catheterization, however this is an invasive and resource intense study. Early identification of pulmonary vascular disease offers the opportunity to improve outcomes by instituting therapies that slow, reverse, or potentially prevent this devastating disease. Multimodality imaging, including noninvasive modalities such as echocardiography, computed tomography, ventilation perfusion scans, and cardiac magnetic resonance imaging, has emerged as an integral tool for screening, classifying, prognosticating, and monitoring response to therapy in PH. Additionally, novel imaging modalities such as echocardiographic strain imaging, 3D echocardiography, dual energy computed tomography, FDG-PET, and 4D flow magnetic resonance imaging are actively being investigated to assess the severity of right ventricular dysfunction in PH. In this review, we will describe the utility and clinical application of multimodality imaging techniques across PH subtypes as it pertains to screening and monitoring of PH.